Literature and the encounter with immanence - Swenson, Brynnar. (Value Inquiry Book Series, 2017)
In Literature and the Encounter with Immanence Brynnar Swenson collects nine original essays that approach the relationship between literature and immanence through methodologies grounded in the philosophy of Spinoza. One of Spinoza's most provocative claims is a simple declaration of ignorance: "We do not know what a body can do." A literary theory based on immanence privileges the ontological status of the text and the material act of reading. Rather than ask what a text means, the essays here ask what a text can do. Each essay documents a distinct literary and philosophical encounter with immanence and, as a result, opens up a space to read literature as one would read philosophy and vice versa .